If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8(y + 9) = -48 Reorder the terms: -8(9 + y) = -48 (9 * -8 + y * -8) = -48 (-72 + -8y) = -48 Solving -72 + -8y = -48 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '72' to each side of the equation. -72 + 72 + -8y = -48 + 72 Combine like terms: -72 + 72 = 0 0 + -8y = -48 + 72 -8y = -48 + 72 Combine like terms: -48 + 72 = 24 -8y = 24 Divide each side by '-8'. y = -3 Simplifying y = -3
| 52=4u+8 | | 0.06x+0.09(15-x)=0.07*15 | | -2x=-4x-6 | | 5a+-10=10(a+3) | | (3-x)/20=2/5 | | 1/3(2x-3)=(2-4x) | | 3x^2y+2y=12 | | 7x-15=6x+8 | | 7=2b-3 | | 4x+11=41 | | 0.06x+0.09(15-x)=0.07 | | 3x-4=9-2x | | 2x=-4x-6 | | 6(2-7r)=-27 | | 15-3s=3 | | 91=4u+15 | | 13x=145 | | 9b-10-8b=-13 | | 16-7s=-9s-20 | | 2x(4x+1)=7 | | 10x-3+3x+5=186 | | 27-9h=-4(5h-2) | | 11x=-9 | | 16-7s=9s-20 | | f(x)=x-4/x(x-4) | | 8=8(w-5)+4w | | 2/5x-16=-6 | | 0.675*t^2-2*t+2=0 | | 2(2k+1)x+5(2k+1)y-3k-1=0 | | 1/3(2x-3)3/4(2-4x) | | 20=3(y+4)-7y | | 6x+4=7x-19 |